Hydraulic Barriers in Soil and Rock 1985
DOI: 10.1520/stp34573s
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Wall Versus Flexible-Wall Permeameters

Abstract: Permeameters are of two general types: fixed-wall and flexible-wall cells. A controversy has developed over which type of cell is best suited for measuring the hydraulic conductivity of relatively impermeable, fine-grained soils. The various types of permeameters are discussed and their relative advantages and disadvantages are listed. Differences in applied stress, boundary leakages, and degree of saturation are the major differences between cells. It is concluded that no one type of cell is best suited to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Daniel et al (1985) indicated that increasing effective stresses could affect the hydraulic conductivity results, particularly for specimens with pre-existing cracks. On the other hand, Fernandez and Quigley (1985) conducted RWP tests that featured very high effective stresses and hydraulic gradients (hydraulic gradients as high as 1000) and yet, they observed substantial changes in hydraulic conductivity due to chemical changes.…”
Section: Comparison With Existing Test Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Daniel et al (1985) indicated that increasing effective stresses could affect the hydraulic conductivity results, particularly for specimens with pre-existing cracks. On the other hand, Fernandez and Quigley (1985) conducted RWP tests that featured very high effective stresses and hydraulic gradients (hydraulic gradients as high as 1000) and yet, they observed substantial changes in hydraulic conductivity due to chemical changes.…”
Section: Comparison With Existing Test Methodsmentioning
confidence: 99%
“…These structural changes in the soil could result in large increases in hydraulic conductivity. In FWPs, however, the soil specimen can freely consolidate under similar chemical stresses, which may hinder the fabric changes and possible fracturing of soils (Daniel et al 1985). This behaviour is evident in the measurements of volume changes of the soil specimen during the tests (Rahman 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil was constrained against swelling. The clay soil has been saturated under a 0.3-bar pressure [14,15]. Experimental setup is given in Figure 1.…”
Section: Permeability Testsmentioning
confidence: 99%
“…Various researchers have tried to evaluate hydraulic conductivity of soils by conducting either laboratory experiments (Bjerrum and Huder 1957;Daniel et al 1985;Chapuis 1990;Fleureau and Taibi 1995;Huang et al 1995;Uno et al 1995) or in situ studies (Bouma et al 1971;Daniel and Trautwein 1986;Little et al 1995;Ankey et al 1991). These methods have been classified as direct methods and indirect methods.…”
Section: Introductionmentioning
confidence: 99%